Health evaluation: the level of implantation of the tuberculosis program in primary health care - Sandy Yasmine Bezerra e Silva; Ewerton William Gomes Brito; Maria de Lourdes Costa da Silva; Aline Ale Beraldo; Nilba Lima de Souza; Érika Simone Galvão Pinto (Universidade Estadual de Maringá, 2023)
The aim of this study is to analyze the level of implantation of the Tuberculosis Control Program in Primary Health Care in a medium-sized city. Normative evaluation study, with a quantitative approach, emphasizing the level of implantation of programs. The sample included 80 nurses and data collection took place from November 2017 to March 2018, using a questionnaire with 62 questions. To identify the level of implantation, the percentage of responses identified was distributed in four classifications: not implanted (from 0% to 25%); incipient (from 26% to 50%); partially implanted (from 51% to 75%) and implanted (from 76% to 100%). The Tuberculosis Control Program in the city was classified as partially implanted (62.85%). The dimensions Structure and Process were also evaluated as being in the same level (61.80% and 63.17%, respectively). The level of implantation of the program was classified as partially implanted, showing shortcomings with regard to the activities developed in the city. Health professionals are expected to make decisions to improve the program.